Anti-frosting operation and regulation technology of air-water dual-source heat pump evaporator. (1st September 2022) - Zhong, Huihui; Zeng, Li; Long, Jibo; Xia, Kuiming; Lu, Haolin; Yongga, A.
Abstract: In this study, a dual-source heat pump evaporator was designed using hot water and air as the heat sources. The hot water coil and the refrigerant coil in the evaporator were arranged in sequence along the air flow direction. The air temperature, relative humidity and velocity at the evaporator inlet, and evaporator hot water temperature were taken as the input parameters. The heat and mass transfer model of the dual-source evaporator was established. Based on the 90% relative humidity(RH) line of the psychrometric chart, the relationship between the refrigerant evaporation temperature and the air absolute humidity ratio under the critical frosting condition of the evaporator was fitted. In the cold season, the evaporator anti-frosting performance under the dual-source condition was tested experimentally and simulated. The results showed that the experimentally determined evaporator temperature was in good agreement with the simulated values. Besides, increasing the evaporator hot water temperature or inlet air velocity enabled one to improve the evaporator fin surface temperature. In particular, when the evaporator working temperature rose above the critical frosting temperature, the anti-frosting operation of the evaporator in winter could be achieved. If the ambient temperature was below 0 °C, the anti-frosting was provided by adjusting the refrigerant evaporation temperature. Highlights: The critical frosting condition of the air source heat pump evaporator was analyzed. The air-water evaporator heat transfer unit model was established. Passing water improved the anti-frosting performance of the dual-source evaporator. The anti-frosting performance improved by increasing the air velocity.